Практика Європейського суду з прав людини щодо експертиз у кримінальному провадженні - Крикунов, О.; Карпінська, Н.; Krykunov, A.; Karpinska, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено прецедентну практику Європейського суду з прав людини щодо оцінки дотримання права особи на справедливий характер кримінального провадження у контексті застосування таких засобів доказування обставин конкретного провадження, як висновок експерта та його показання. Встановлено, що непроведення судової експертизи цим Судом визнається невиконанням державою обов’язку провести ефективне розслідування злочину; узагальнено підходи до критеріїв компетентності та незацікавленості особи експерта; право сторін на допит експерта.The article explores the case-law practice of the European Court on Human Rights regarding the assessment of the observance of the person’s right on the fair criminal proceedings, implying the use of the expert’s conclusion and his testimony as a means of proving the circumstances of the proceedings. The author assumes that the failure to conduct forensic examination in the Court proceedings can be interpreted as the failure of the State to conduct an effective investigation of the crime. The author summarizes upon the following: the approaches of the European Court on Human Rights to the criteria of expert’s competence or expert’s lack of interest in investigation of a crime; the importance of expert’s opinion in determining whether the person can speak in his own defense. It has been found out that by analogy the European Court on Human Rights ascertained the right of the parties to cross-examine the expert.
Practice of European Court of Human Rights on the Expertise in Criminal Proceeding
Keywords: Практика Європейського суду з прав людини; висновок експерта; право на справедливий судовий розгляд; право на повагу до таємниці приватного життя; кримінальне провадження; European Court on Human Rights; an expert’s opinion; the right to a fair trial; the right to respect for privacy; criminal proceeding